To compare the perinatal outcome of IUGR infants with abnormal and normal antenatal umbilical artery Doppler flow in the immediate neonatal period - B., Shivaprasad; Sharma, Devendrakumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Intrauterine growth restriction (IUGR) is one of the cause of perinatal mortality and morbidity and affects approximately 7-15% of worldwide pregnancies. IUGR is the failure of the fetus to achieve intrinsic growth potential, due to disorders and diseases in the feto–placental–maternal unit. Doppler indices from the fetal circulation can reliably predict adverse perinatal outcome. Aim of the study was to determine perinatal outcome of IUGR infants with abnormal antenatal umbilical artery Doppler flow versus IUGR infants with normal Doppler flow. Methods: All Preterm and term IUGR infants with abnormal and normal antenatal umbilical artery Doppler scan admitted in NICU of St Martha’s Hospital were included in the study. 30 in each group with total sample size of 60. Study was conducted from March 2015 to February 2016. Primary outcome measure will be neonatal mortality and secondary outcome measure will be neonatal morbidities like perinatal asphyxia, hypoglycemia, NEC, polycythemia, sepsis, hyperbilirubinemia etc. Results: IUGR infants with abnormal antenatal umbilical artery Doppler scan were included as cases and those with normal antenatal umbilical artery Doppler scan as control. At birth resuscitation rate and therefore perinatal asphyxia was observed more in case group, 11 out of 30 (36.6%), compared to 1 out of 30 (3.3%) in control group, statistically significant (P <0.05). Hypoglycemia was noticed in 19 infants in case group (63.3%) compared to 2 infants (6.6%) in control group, statistically significant. NEC, polycythemia, sepsis was noticed more in case group, but statistically not significant. Conclusions: Infants with abnormal antenatal Doppler flow are at increased risk of perinatal complications than infants with normal antenatal umbilical artery Doppler and needs extra care during this period.